PENGARUH DUKUNGAN KELUARGA DAN TENAGA KESEHATAN TERHADAP KELENGAPAN IMUNISASI DASAR PADA BAYI 6- 12 BULAN DI PUSKESMAS KUTATAHUN 2023 - Baiq Reni Pratiwi; Harun Ningsih (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Immunization is one of the preventive ways to prevent disease through the provision of immunity which must be given continuously, thoroughly and implemented according to standards so as to provide health protection and break the chain of transmission. Family opinion also affects compliance in the completeness of basic immunizations. If opinions in a family are low then those opinions take precedence for the basic needs of the family rather than for efforts design used was an analytical survey study with a cross sectional approach to determine the effect of family support and health support on the completeness of basic immunization in infants aged 6-12 months. The results of the chi-square test show that significant p value = 0.002 (p value < 0.05). Which shows that there is a relationship between family support and the completeness of basic immunization in children aged 6 -12 months at the Kute Health Center in 2023. The results of the chi-square test show that the p value (sig) = 0.001 shows that there is a relationship between health worker support and the completeness of basic immunization in children 6 -12 months old at the Kute Health Center in 2023.